2012
DOI: 10.3747/co.19.879
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of a Metronomic Schedule of Docetaxel and Capecitabine with Concurrent Celecoxib in Patients with Prior Anthracycline Exposure for Metastatic Breast Cancer

Abstract: Background: This phase II clinical trial examined the activity of a metronomic dosing schedule of docetaxel and capecitabine chemotherapy in patients with advanced breast cancer. Patients also received daily oral celecoxib in an effort to improve outcome measures and to ameliorate some of the common side effects of chemotherapy. Methods: Patients received docetaxel at a starting dose of 15 mg/m2 weekly, oral capecitabine 1250 mg/m2 once daily, and oral celecoxib 200 mg twice daily. The primary endpoint was cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Cyclophosphamide (Cy), is one of the most used drugs in cancer treatment and is one of the earliest cytotoxic drugs used in MCT [13]. Celecoxib (Cel), a selective Cyclooxygenase 2 inhibitor, has shown antitumor activity for breast cancer cell lines, not only in-vitro but also in-vivo [14], and its use has been translated to the clinic [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide (Cy), is one of the most used drugs in cancer treatment and is one of the earliest cytotoxic drugs used in MCT [13]. Celecoxib (Cel), a selective Cyclooxygenase 2 inhibitor, has shown antitumor activity for breast cancer cell lines, not only in-vitro but also in-vivo [14], and its use has been translated to the clinic [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other trials have used other approaches. [26][27][28][29][30] The fulvestrant arm in the Evaluation of Faslodex versus Exemestane Clinical Trial (EFECT) trial reported by Chia and colleagues was comparable to the fulvestrant schedule in this study. 4 Chia et al reported a median TTP of 3.7 months, 4 compared with 26.94 months (95% CI, 7.26 months-upper limit not estimated) for the current sample.…”
Section: Discussionmentioning
confidence: 49%
“…In this trial, the outcome measures were similar to those obtained when the study agents are dosed in a c onventional manner. 106 Metronomic chemotherapy was investigated in combination with endocrine therapy. The activity of fulvestrant (250 mg given by intramuscular injection every 28 days) in combination with oral metronomic chemotherapy was evaluated in two cohorts of 33 postmenopausal patients with heavily pre-treated ER-positive advancedstage breast cancer.…”
Section: Metronomics In the Metastatic Settingmentioning
confidence: 99%